Extraction, Characterization and Antimicrobial Properties of Pigments from Yeast, Rhodotorula mucilaginosa Isolated from the Mangrove Sediments of North Kerala, India - Vidya, Pothayi; Kutty, Sreedevi Narayanan; Sebastian, Chempakassery Devasia (Asian Journal of Biological and Life Sciences)
Carotenoids are natural pigments having important role in food, feed, pharmaceutical and cosmetic industries. Their role as strong antioxidant and essential food coloring agent has received major attention during recent years. Though carotenoids are present in plants and animals, its production from microbes are more advantageous due to their faster growth rate, cheaper cultural requirements, ease of manipulation and extraction, and safety considerations. Among the microbes, pigmented yeasts are found to be the most reliable candidates for the large scale production of carotenoids due to their higher rate of growth and simple unicellular structure. In our study, pigmented yeasts, Rhodotorula mucilaginosa were screened, isolated and identified from mangrove sediments of various sites along North Kerala. The pigments were extracted using DMSO-acetone solvent in to petroleum ether and characterized using UV-Visible spectrophotometer and NMR spectrophotometer. The pigment present in R. mucilaginosa was found to be β-carotene. The antimicrobial effect of the extracted pigment and the whole yeast isolate was tested against potent pathogens Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, Salmonella typhi, and Streptococcus pyogenes using disk diffusion method. Antimicrobial activity in the form of inhibition zone was shown by the extracted carotenoid against Staphylococcus aureus. Also, the optimization of growth conditions for maximum biomass yield and hence maximum carotenoid production was also studied. R. mucilaginosa was found to have highest growth at pH 7, with 5 ppt salt concentration at 25°C in malt extract broth and these conditions can be employed in their fermentation process for the large scale production of carotenoids.
Keywords: Antimicrobial activity; Carotenoids; Mangrove sediments; Optimization; Rhodotorula mucilaginosa; β-carotene